Editors’ Introduction - Vršnik Perše, Tina (Revija za elementarno izobraževanje, 2025)
This special issue of the Journal of Elementary Education addresses the topic of healthy lifestyles in the context of sustainable development and lifelong learning. It is based on content developed as part of the Healthy Lifestyle for Sustainable Development and Lifelong Learning project, implemented by the Faculty of Education, University of Maribor (The project is part of the national Recovery and Resilience Plan (NOO) and is co-financed by the European Union’s Recovery and Resilience Facility). The focus is on striving for a holistic approach to understanding the factors under consideration and the relationships between them, contributing to the well-being of individuals and society.In recent years, a healthy lifestyle has become a topic of discussion at the interface between science, policy, and everyday life. The chosen topic goes beyond individual disciplines and signals a shift in understanding healthy lifestyles and well-being as complex and dynamic processes that go beyond physical and motor aspects, holistically treating the individual. It encompasses reflections on physical, mental, and social balance, cultural and environmental aspects of life, the importance of creativity and belonging, and how an individual establishes relationships with the self, others, and their surroundings. Precisely because of its complexity, the topic is relevant from the scientific research perspective and in its quest for answers to practical, systemic, and long-term challenges. The papers in this issue highlight various aspects of a healthy lifestyle and well-being by analysing physical, mental, social, and environmental factors. The authors address issues related to a range of life stages (from early childhood through school years, and higher education to professional development), contexts, and professional foundations. They examine topics related to physical activity, dietary habits, the use of digital technology, nature, art, emotional responses, the sense of safety, and the well-being of both children and adults.The authors Loudová Stralczynská, Lipnicka, and Chytrý examine preschool teachers’ views from the Czech Republic and Slovakia on the criteria for admitting two-year-olds to kindergarten. They highlight the tension between institutional expectations and children’s developmental characteristics and emphasise the importance of child-centred, developmentally appropriate practices that promote children’s well-being. Pölzl-Stefanec and Gutmann analyse the inclusion of children in kindergarten from the parents’ perspective. Using the concept of sense of coherence, they identify both stressors and sources of support in the process of introducing children to preschool and emphasise the importance of cooperation between preschool institutions and families as a basis for the child’s well-being and sustainable integration into institutional settings. Kobler discusses the importance of the natural environment, especially the forest, for developing resilience and well-being in preschool children in today’s often stressful world. She presents the forest as an experiential space that positively impacts children’s emotional stability, physical health, and social connectedness, shaping sustainable attitudes in early childhood. The role of art in preschool education is compared by the authors Štirn Janota and Dýrfjörð, using examples from Slovenia and Iceland. They place art at the centre of the educational process as a factor in creativity, reflection and community that strengthens emotional well-being and lays the foundation for sustainable coexistence. They also recognise that both students and educators need educational programs that integrate health, well-being, and art. Authors Komzáková and Koželuhová pay particular attention to the role of transitional objects and rituals used by primary school teachers to support students’ emotional well-being. Their contribution highlights the importance of a safe, engaging learning environment, along with attention to children’s emotional needs during the transition to compulsory education and in the early school years. Also at the level of early primary education, Jančič Hegediš examines the teaching of social studies outside the classroom. She emphasises the importance of experiential outdoor learning that promotes active student participation, stimulates curiosity, and contributes to forming a sustainable mindset and a sense of well-being as a physical and environmental learning experience. Fošnarič and Dolenc explore a different aspect in the same age group: the influence of digital technology on children’s daily habits related to physical activity, nutrition, sleep, and mental health. They emphasise the need for a balanced approach and cross-sectoral cooperation in creating an environment that supports a healthy lifestyle for children in a digitised everyday world. Matejek and Kukovica examine differences in body composition and lifestyle habits between normal-weight and overweight or obese trainee teachers. Using a combination of questionnaires and body composition measurements, they investigate the interplay between perceived and objective aspects of lifestyle among university students. They conclude that it would be helpful to develop targeted programs to promote a healthy lifestyle at universities, particularly for future teachers, who play a key role in shaping healthy habits among school students. Prskalo and Planinšec, working with the same target group, analyse the relationship between physical activity, sedentary behaviour, and academic success among students. Their paper encourages reflection on the balance between learning, movement, and rest, and calls for a holistic understanding of health and success in the university environment. Also with the same target group, Vršnik Perše and Grafenauer Ekart analyse the relationship between student well-being and factors such as social and mental balance, physical activity, dietary habits, and daily routines. The paper fits into a broader framework of reflection on a holistic approach to a healthy lifestyle among youth. It emphasises the need for sustainable supportive environments that promote psychological, physical, and social well-being among students. Educational professionals are a key factor in raising awareness of a healthy lifestyle. Poche Kargerová, Göbelová, Šimlová and Seberová present the WANDA method as a structured approach to group reflection for educators. The paper highlights the importance of professional support, collegial learning, and concern for staff well-being as the foundation of sustainable and high-quality educational practice. Despite the methodological and content diversity of these contributions, they share a common ground. Health, well-being, and sustainability are not concepts to be addressed in isolation but must be understood as interwoven, interdependent, and embedded in a broader social and cultural context. The scientific papers in this issue make a valuable contribution to understanding complex relationships by placing them within the broader framework of lifelong learning. The international contributions provide an additional scientific contribution to the topic of healthy lifestyle in relation to sustainable development and lifelong learning, offering insights from diverse societal perspectives. We believe this thematic issue will stimulate reflection on the links between research, everyday practice, and systemic design of conditions aimed at a lifelong development of quality, safe, and healthy lives.